Antibacterial properties of lactoferrin: A bibliometric analysis from 2000 to early 2022 - Xu, Yunling; Wang, Yuji; He, Jiaolong; Zhu, Wanping (Frontiers in Microbiology, 2022)
Background: Here, a bibliometric and knowledge-map analysis are used to analyze the research hotspots and development trends regarding the antibacterial effect of lactoferrin (LF). By looking for research hotspots and new topics, we provide new clues and research directions for future research. Methods: Articles and reviews regarding the antibacterial effect of LF were retrieved and from the Web of Science Core Collection (WoSCC) on April 4, 2022. CiteSpace and VOSviewer were used to conduct the bibliometric and knowledge- map analysis. Results: In total, 8079 authors at 2078 institutions from 84 countries published 1862 papers in 760 academic journals. The United States was the leader regarding research on the antibacterial effects of LF, while the Netherlands was a pioneer conducting research in this field. The University of California system contributed the most publications. Bolscher JGM published the most articles, while Wayne Bellamy had the most cocitations. However, there was little cooperation among countries and the various institutions. Biometals published the most LF-antibacterial activity-related papers, whereas Infection and Immunity was the most commonly cocited journals. The most influential research hotspots about the antibacterial effect of LF focused on antimicrobial peptides, Escherichia coli-related research, lysozyme and binding. The latest hotspots and research frontier included Covid-19, antibiofilm activity and immune defense. Conclusions: LF is a multifunctional protein with a broad-spectrum of antimicrobial activities. The related field of antibacterial properties of LF will remain a research hotspot in the future.